Career transition : the sport retirement experiences of New Zealand athletes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Smith, Andrea J (Massey University, 1999)
This study explored the sport retirement experiences of seventy-four New Zealand athletes who were identified as having retired from high performance sport participation. During the peak of their sport careers, these athletes achieved regional, national, or international competitive representation. The Athlete Career Transition Inventory, a 47-item instrument, was developed for this study. The inventory was divided into sections that examined: motivation for sport participation, reasons for retirement, adjustment to retirement, pre-retirement career planning, social networks, athlete identity dimensions, and life satisfaction. Analysis indicated the majority of athletes adjusted to their sport retirement with minimal difficulty. Although significant differences between the gender groups were only observed for sense of personal control at transition X2 (2, n = 72) = 6.66, p = .036, there appear to be differences between male and female athletes with regard to social support prior to transition. Neither goal achievement nor the causal factors involved in the retirement decision predicted the quality of the athlete's adaptation experience. Practical implications for coaches and sport bodies are discussed.
Keywords: Athletes; Retirement; Psychology; Psychological aspects; Career changes; New Zealand